Cytotoxic Evaluation and Anti-Angiogenic Effects of Two Furano-Sesquiterpenoids from Commiphora myrrh Resin - S. Alqahtani, Ali (Molecules, 2020)
Commiphora myrrh resin (Myrrh) has been used in traditional Arabic medicine to treat various inflammatory diseases. Two furano-sesquiterpenoids, 2-methoxyfuranodiene (CM1) and 2-acetoxyfuranodiene (CM2), were isolated from the chloroform fraction of the ethanolic extract of Arabic Commiphora myrrh resin. The cytotoxicity of the compounds was evaluated using human liver carcinoma, breast cancer cells (HepG2 and MCF-7, respectively) and normal human umbilical vein endothelial cells (HUVECs) cell lines. The development toxicity and anti-angiogenic activity of both compounds were also evaluated using zebrafish embryos. Cell survival assays demonstrated that both compounds were highly cytotoxic in HepG2 and MCF7 cells, with IC(50) values of 3.6 and 4.4 µM, respectively. Both compounds induced apoptosis and caused cell cycle arrest in treated HepG2 cells, which was observed using flow cytometric analysis. The development toxicity in zebrafish embryos showed the chronic toxicity of both compounds. The toxicity was only seen when the embryos remained exposed to the compounds for more than three days. The compound CM2 showed a significant level of anti-angiogenic activity in transgenic zebrafish embryos at sublethal doses. Thus, we demonstrated the cytotoxic properties of both compounds, suggesting that the molecular mechanism of these compounds should be further assessed.